Clinical Outcomes and Complications of Endoscopic Submucosal Dissection for Superficial Gastric Neoplasms in the Elderly. Issue 44 (November 2015) - Yang, Tsung-Chieh; Hou, Ming-Chih; Chen, Ping-Hsien; Hsin, I-Fang; Chen, Liang-Kung; Tsou, Mei-Yung; Lin, Han-Chieh; Lee, Fa-Yauh
Abstract : Abstract: The number of elderly people with superficial gastric neoplasms is increasing, but the clinical outcome of endoscopic submucosal dissection (ESD) for treating elderly people with superficial gastric neoplasms remains unclear. We aimed to compare the efficacy and safety of ESD for patients with early gastric cancer (EGC) and precancerous lesions in elderly (≥75 years of age) and nonelderly (<75 years of age) patients. From October 2005 to December 2014, 83 consecutive patients with EGC and precancerous lesions (86 lesions) who were treated using ESD in our hospital were retrospectively reviewed. There were 44 lesions in 42 elderly patients who were at least 75-years old. The following parameters were compared between the 2 groups: preexisting comorbidities, performance status (PS), lesion inclusion criteria, lesion characteristics, treatment outcomes, surgery time, duration of hospitalization, complications, and intraoperative hemodynamic changes. Elderly patients had significantly higher preexisting comorbidity rates (90.9% vs 59.5%, P = 0.001), expanded lesion criteria rates (43.2% vs 19.0%, P = 0.016), and lower best PS rates (38.6% vs 81.0%, P < 0.001) than nonelderly patients. Lesion characteristics were similar in the 2 groups. The elderly had higher intraoperative hypotension rates (47.7% vs 21.4%, P = 0.011) and oxygen desaturation rates (9.1% vs 0.0%, P = 0.045) than nonelderly patients. In addition, the elderly also had a longer surgery time (107.0 ± 51.4 vs 91.5 ± 66.2 minutes, P = 0.049) and duration of hospitalization (7.5 ± 3.8 vs 5.9 ± 2.0 days, P = 0.016) than nonelderly patients. There were no differences in the prevalence rates of en-bloc resection, complete resection, bleeding, perforation, pneumonia, or intraabdominal free air between the 2 groups. Although elderly patients who underwent ESD for superficial gastric neoplasms had an increasing risk of intraoperative hypotension and oxygen desaturation, all patients were treated appropriately without postoperative sequelae. ESD is a safe and feasible intervention for elderly patients who have more comorbidity, a worse PS and more expanded lesions.